Neural and muscular factors both contribute to plantar-flexor muscle weakness in older fallers - Cattagni, Thomas; Harnie, Jonathan; Jubeau, Marc; Hucteau, Elyse; Couturier, Catherine; Mignardot, Jean-Baptiste; Deschamps, Thibault; Berrut, Gilles; Cornu, Christophe (Experimental gerontology, 2018)
Plantar-flexor muscles are key muscles in the control of postural sway. Older fallers present lower maximal plantar-flexor performance than older non-fallers; however, the mechanisms underlying this motor impairment remain to be elucidated. This study aimed to determine whether muscular and neural factors are both involved in the lower maximal plantar-flexor performance of older fallers. The maximal voluntary contraction (MVC) torque, resting twitch torque, voluntary activation level (VAL), and electromyographic (EMG) activities for the soleus, gastrocnemius medialis, gastrocnemius lateralis and tibialis anterior during plantar-flexor MVCs were recorded in 23 older non-fallers (age: 83.3 ± 3.9 years) and 25 older fallers (age: 84.0 ± 4.1 years). The maximal plantar-flexor Hoffmann reflex normalized to the maximal motor potential (Hmax/Mmax) was measured to assess the efficacy of spinal transmission from the Ia-afferent fibers to the α-motoneurons. Older fallers presented lower plantar-flexor MVC torque, resting twitch torque, VAL and EMG activity (P < 0.05). No significant differences between older fallers and non-fallers were found for the Hmax/Mmax ratio and dorsi-flexor coactivation. The current findings showed for the first time that both neural and muscular factors associated with the plantar-flexors contributed to the specific alteration of maximal motor performance in older fallers. The lack of a difference in the Hmax/Mmax ratio indicated that the efficacy of spinal transmission from the Ia-afferent fibers to the α-motoneurons was not involved in the lower voluntary muscle activation of older fallers. This suggests that supraspinal centers are likely to be involved in the lower voluntary muscle activation observed in older fallers. •This study provides the plantar-flexor neuromuscular profile of older fallers.•Older fallers present a lower maximal plantar-flexor torque than older non-fallers.•Muscle and neural mechanisms are both involved to this muscle weakness.